Wolman's Disease: A Rare Cause of Infantile Cholestasis and Cirrhosis - Menon, Jagadeesh; Shanmugam, Naresh; Srinivas, Sripriya; Vij, Mukul; Jalan, Anil; Srinivas Reddy, Mettu; Rela, Mohamed (Journal of Pediatric Genetics, 2020)
Liver cirrhosis in infancy can be secondary to various etiologies such as biliary atresia, familial cholestatic and metabolic disorders. Wolman's disease (WD) is a lysosomal storage disorder caused by the absence of lysosomal acid lipase enzyme activity and a significant association with infantile cholestasis and cirrhosis. We encountered an infant presenting with advanced cirrhosis and decompensation having splenomegaly for which the underlying etiology was found to be WD and the diagnostic clue came from abdominal X-ray showing bilateral adrenal calcifications. The diagnosis was confirmed by genetic analysis. The outcome was poor and died before 6 months of age without enzyme replacement therapy or hematopoietic stem cell transplantation.
Keywords: Wolman's disease; infantile cholestasis; cirrhosis; adrenal calcification